Estimating bisphenol A exposure levels using a questionnaire targeting known sources of exposure. Issue 4 (2nd July 2015) - Nomura, Sarah Oppeneer; Harnack, Lisa; Robien, Kim
Abstract: Objective: To develop a BPA Exposure Assessment Module (BEAM) for use in large observational studies and to evaluate the ability of the BEAM to estimate bisphenol A (BPA) exposure levels. Design: The BEAM was designed by modifying an FFQ with questions targeting known sources of BPA exposure. Frequency of intake of known dietary sources of BPA was assessed using the BEAM and three 24 h food records as a reference diet measurement tool. Urinary BPA (uBPA) levels were measured as the criterion tool in a pooled urine sample (nine spot samples per participant). Spearman correlations, linear regression and weighted kappa analysis were used to evaluate the ability of the BEAM and food records to estimate BPA exposure levels. Setting: Minneapolis/Saint Paul, MN, USA. Subjects: Sixty-eight healthy adult (20–59 years) volunteers. Results: Dietary BPA intake assessed by the BEAM was not associated with uBPA levels and was unable to predict participants' rank by uBPA levels. BEAM models with all a priori predictors explained 25 % of the variability in uBPA levels. Canned food intake assessed by food records was associated with uBPA levels, but was unable to rank participants by uBPA levels. Multivariable-adjusted food record models with a priori predictors explained 41 % of the variability in uBPA levels. Conclusions: Known dietary sources of BPA exposure explained less than half the variability in uBPA levels, regardless of diet assessment method. Findings suggest that a questionnaire approach may be insufficient for ranking BPA exposure level and additional important sources of BPA exposure likely exist.